Immaterial Indigenous Modernities in the Struggle against Illegal Fencing in the N≠a Jaqna Conservancy, Namibia: Genealogical Ancestry and 'San-ness' in a 'Traditional Community'. Issue 2 (4th March 2019) - van der Wulp, Christa; Koot, Stasja
Abstract : For several years, livestock farmers from different parts of Namibia have settled in the N≠a Jaqna Conservancy – an area mostly inhabited by San (Bushmen) – and have illegally erected fences to keep livestock. As a result of this encroachment, communal land in N≠a Jaqna has become de facto privatised. In response, the local San present themselves as the 'indigenous' inhabitants, even though many of them do not originate from the area. They have mobilised the Conservancy as their legal entity – including in a court case – despite Namibia's lack of a legal framework for the recognition and enforcement of global indigenous rights. We analyse their strategic usage of 'traditional community', which is a legal term in Namibia, in this land politics. To this aim, we use the four core pillars (characteristics) of the global concept of 'indigeneity', namely genealogical ancestry, cultural difference (in this case 'San-ness'), non-dominance and self-ascription, with specific emphasis on the first two. Whereas genealogical ancestry appears to be a 'weak' argument for the San at first glance, cultural difference (supported by non-dominance and self-ascription) has proven crucial to winning the court case. We show that the use of 'traditional community' enables these four pillars to play an important role in defining who has access to the land and its resources. As such, we argue, traditional community and indigeneity (even though the latter is not formally acknowledged) provide the San of the N≠a Jaqna Conservancy with 'immaterial indigenous modernities': modern values or ideas in society that can be used strategically by local, marginalised groups to reach political goals.